Կրթական վերջնարդյունքի գնահատման մեթոդը աշխարհագրության դպրոցական դասագործընթացում - Բաբայան, Տ. Հ. (Մանկավարժ հրատ․)
Աշխարհագրական կրթական համակարգի ներկա հրամայականն է՝ ուսուցման գործընթացը կազմակերպել տեղեկատվական տեխնոլոգիաների և հատկապես երկրատեղեկատվական համակարգերի ուսումնասիրման հենքի վրա: Ուսուցանողուսումնառող գործընթացի լավագույն կառավարողը ինքնագնահատականն է: Վերջնարդյունքահեն գնահատումը էական է սովորողների հետ նպատակամղված աշխատանքը ճիշտ պլանավորելու և ուսումնառության գործընթացում յուրօրինակ մոտեցումներ մշակելու, սովորողների ու ուսուցիչների միջև ռեֆլեքսիվ իրազեկման գործընթաց ձևավորելու համար: Հոդվածի գիտական նորույթն է՝ կյանքից վերցված հիմնահարցերի ու ժամանակակից տեխնոլոգիական նվաճումների վրա կառուցված առաջադրումները, ուր առկա են նաև միջգիտակարգային կապերի կիրառումը, սովորողների կողմից շրջապատը յուրովի ընկալելու, դրանցում առկա տարածական կապերը բացահայտելու և ինքնակրթվելու լուրջ խթան են: В настоящее времья в основ задачей системы географического образования является организация учебного процесса на основе информационных технологий, особенно с помощью географических информационных систем (ГИС). Лучшим определяющим учебнопедагогического процесса является самооценка. Оценкой конечного результата становится целенаправленное планирование работы с учащимися, выработка новых подходов к обучению, создание процесса рефлексивного осознания между учениками и учителем. Задачи взятые из жизненных ситуаций, и решения на современных технологических достижениях, где также используются междисциплинарные связи, могут быть серьезным стимулом для учащихся к восприятию окружающей среды, к обнаружению существующих пространственных связей, то есть к самообразованию. Необходимость развития информационной культуры учителей сегодня составляет основу социальных ценностей каждого общества. Современный педагог нуждается не только в высоком уровне профессиональной, психологической, педагогической компетентности, но и в инновационных подходах и умениях для творческой организации своей деятельности. Приведен пример географической задачи, способствующий усвоению темы «Основные методы географических исследований» курса 10 класса и ее решение. The current task of the geographic education system is to organize the educational process on the basis of information technologies, especially with the help of geographic information systems (GIS). The best manager of the educational and pedagogical process is self-assessment. The assessment of the final result is the purposeful planning of work with students or students, the development of unique approaches to learning, the creation of a process of reflective awareness between students and teachers. Tasks based on life problems, and solutions based on modern technological advances, where interdisciplinary connections are also used, can be a serious incentive for students to perceive the environment, to discover existing spatial relationships, that is, to self-education. The need to develop the information culture of teachers today forms the basis of the social values of every society. A modern teacher requires not only a high level of professional, psychological, pedagogical competence, but also innovative approaches and skills for the creative organization of their activities. Here is an example of a geographic problem that contributes to the assimilation of the topic "Basic methods of geographical research" course of grade 10 and its solution. After familiarization with the expected requirements of the topic, the lesson material is studied taking into account the criteria, and we determine the final results from the planned course. Bloom's classification (Bloom1956) is used as a criterion. This allows you to organize the learning process in such a way that students apply their knowledge at all 6 levels of cognitive development, from simple to complex. B. Bloom classification is a hierarchical classification of cognitive abilities educational achievements. Basically it is presented in the form of a pyramid, from simple to difficult levels, developing towards the top. The teacher can use this pyramid to assess the difficulty level of lesson planning as well as their abilities. New approaches to the assessment process allow the student to understand their achievements / shortcomings in the educational process, contributing to the formation of self-government. For teachers, approaches to the final assessment help to constantly check the assimilation of the course, get the general outline of the curriculum, the assimilation of a certain topic, laying the foundation for the progress of assimilation of the curriculum. Educational result is a process, not a one-time operation.
Keywords: Աշխարհագրության դասավանդման մեթոդիկա